1997
DOI: 10.1042/bj3270291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the tetraspanin CD9–integrin αIIbβ3 (GPIIb-IIIa) complex in platelet membranes and transfected cells

Abstract: The platelet integrin, alphaIIbbeta3 (GPIIb-IIIa), and the tetraspanin, CD9, are integral membrane proteins that are abundant in platelet membranes. We have identified several proteins, including CD9, which were co-precipitated by anti-alphaIIbbeta3 antibody from untreated, resting platelets that were solubilized with the poly(oxyethylene) non-ionic detergent, Brij-35. Immunoblot and quantitative immunoprecipitation showed that the association of alphaIIbbeta3 with CD9 is specific and stoichiometric. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 50 publications
5
59
0
Order By: Relevance
“…311, Etablissement de Transfusion Sanguine de Strasbourg, Strasbourg, France), an integral membrane protein abundantly present in platelet membranes. 17 The A␤ antibody specifically stained ␤-amyloid deposits in brain tissue from patients with Alzheimer's disease, confirming its specificity. Double-labeling immunohistochemistry was performed to detect colocalization of iNOS or COX-2 with APP, A␤, or CD9.…”
Section: Immunohistochemical Study Of Advanced Human Atherosclerotic mentioning
confidence: 74%
“…311, Etablissement de Transfusion Sanguine de Strasbourg, Strasbourg, France), an integral membrane protein abundantly present in platelet membranes. 17 The A␤ antibody specifically stained ␤-amyloid deposits in brain tissue from patients with Alzheimer's disease, confirming its specificity. Double-labeling immunohistochemistry was performed to detect colocalization of iNOS or COX-2 with APP, A␤, or CD9.…”
Section: Immunohistochemical Study Of Advanced Human Atherosclerotic mentioning
confidence: 74%
“…The ␣IIb␤3 integrin has been reported to be associated with CD9 and other membrane proteins. 32,33 We performed immunoprecipitations with the anti-CD36 antibody on platelets from a patient with Glanzmann thrombasthenia to establish that CD36 associates with the other proteins in the absence of ␣IIb␤3. The platelets from this patient contain about 3% of the normal levels of ␣IIb␤3 and contain normal levels of ␣v␤3.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet CD36 has been reported to associate with ␣IIb␤3 that has, in turn, been reported to associate with CD9. 20,32,33 Dorahy et al 20 showed that CD36 and ␣IIb␤3 could be cross-linked to each other without evidence of inclusion of CD9. Rhinehart-Jones and Greenwalt 25 identified a 113 000-d species that reacts with antibodies to CD36 after platelets are cross-linked with bis (sulfosuccinimidyl) suberate.…”
Section: Discussionmentioning
confidence: 99%
“…They form protein complexes that are mostly composed of different tetraspanins and integrins, but can also contain members of other protein families Horvath et al, 1998;Indig et al, 1997;Lozahic et al, 2000;Mannion et al, 1996;Rubinstein et al, 1997;Scherberich et al, 1998;Serru et al, 1999;Sincock et al, 1999;Tiwari-Woodruff et al, 2001;Yauch et al, 1998). The strongest association between tetraspanins and integrins has been described for CD151 and the α3 and α6 integrins Yauch et al, 1998;Yauch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%